Assegaf, M. I. F., Juliani, H., & Sa’adah, N. (2019). Pelaksanaan Online Single Submission (OSS) Dalam Rangka Percepatan Perizinan Berusaha Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Jawa Tengah. Jurnal Hukum Diponegoro, 8(2), 1328–1342. Aula Izatul Aini, Muhammad Imam Khaudli, & Ribut Suprapto. (1970). Pemberdayaan Ekonomi Masyarakat melalui Pemasaran Wisata Kuliner Jajanan Tradisoional di Desa Cantuk Kabupaten Banyuwangi. Engagement : Jurnal Pengabdian Kepada Masyaraka - Yeny Fitriyani; Rizqi Istiqomah (Khidmatan, 2022)
Several countries, especially Indonesia, are still feeling the Covid-19 pandemic. The Covid-19 pandemic has impacted the health, politics, and education sectors. In addition, the impact felt by the Indonesian state is the economic sector. The Indonesian economy experienced a slump; the government intensified Micro, Small, and Medium Enterprises to improve quality. Because MSMEs are increasingly visible and widely owned by Indonesian citizens, the government provides a policy that every MSME must have legality. This legality is called the Business Permit Number or NIB, formerly known as SIUP. Using the PAR approach, the facilitator conducts a mentoring program for making NIB using the Online Single Submission System so that MSME actors immediately have legality. Moreover, during the making of the NIB, MSME actors access the OSS page and already have a legality called NIB.